2022
DOI: 10.1159/000526947
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gut Microbiota with Mild Cognitive Impairment and Alzheimer’s Disease in a Thai Population

Abstract: Background: Mild cognitive impairment (MCI) and Alzheimer's disease (AD) are common in older adults. Much recent work has implicated the connection between the gut and the brain via bidirectional communication of the gastrointestinal tract and the central nervous system through biochemical signaling. Altered gut microbiota composition has shown controversial results based on geographic location, age, diet, physical activity, psychological status, underlying diseases, medication, and drug use. Objectives: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…MCI patients with more Bacteroides are more likely to present brain atrophy patterns compatible with AD ( Saji et al, 2019a ). Regarding regional brain volume, Wanapaisan et al have discovered associations of left and right-hippocampus and right amygdala volumes with groups of bacteria identified in their study ( Wanapaisan et al, 2022 ). However, they also enrolled AD patients and mainly compared brain volumes in controls with AD/MCI.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…MCI patients with more Bacteroides are more likely to present brain atrophy patterns compatible with AD ( Saji et al, 2019a ). Regarding regional brain volume, Wanapaisan et al have discovered associations of left and right-hippocampus and right amygdala volumes with groups of bacteria identified in their study ( Wanapaisan et al, 2022 ). However, they also enrolled AD patients and mainly compared brain volumes in controls with AD/MCI.…”
Section: Discussionmentioning
confidence: 88%
“…Studies in AD have demonstrated a microbial composition that deviates significantly from that of cognitively normal controls ( Vogt et al, 2017 ; Zhuang et al, 2018 ; Liu et al, 2019 ; Saji et al, 2019a , b ; Guo et al, 2021 ). There is also emerging data about gut microbiota change in MCI patients ( Li et al, 2019 ; Liu et al, 2019 ; Saji et al, 2019a , b ; Guo et al, 2021 ; Pan et al, 2021 ; Sheng et al, 2021 , 2022 ; Zhang et al, 2021 ; Verhaar et al, 2022 ; Wanapaisan et al, 2022 ; Yıldırım et al, 2022 ). In general, similar gut microbiota changes as AD were found in MCI patients, such as decreased Bacteroides genus and increased Staphylococcus and Escherichia ( Li et al, 2019 ; Nagpal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…While Pseudomonadota tends to generally be overrepresented in AD and MCI patients, certain studies suggest somewhat contradictory evidence as some research observed negative correlations between genera such as Sutterella and AD/MCI [ 82 , 83 ] while others observed their positive correlations to AD/MCI [ 52 , 81 , 84 ] . Other genera such as Escherichia/Shigella and Klebsiella are consistently elevated in AD/MCI patients where differences reach significance [ 54 , 81 , 82 , 85 , 86 ] . The general trend of Pseudomonadota overrepresentation in AD/MCI patients may be reflective of the proinflammatory characteristics of LPS; however, inconsistencies such as those found in relative Sutterella abundance may be reflective of other important factors such as differential bacterial metabolic processes at the genus, species, or even strain level and thus effects on host inflammation.…”
Section: Specific Gut Microbiome Signatures Linked To Admentioning
confidence: 99%
“…It was significantly decreased in PD with more intensive inflammation in the intestine [45], which was further identified as a critical biomarker of the progression of PD in another study [46]. In a study of the Thai population, the abundance of Fusicatenibacter was dramatically downregulated in dementia patients [47]. According to the evidence above, we assumed that these two genera contributed to the maintenance of gut-brain axis in relatively healthy individuals and had a positive impact on the recovery of BGRI.…”
Section: Discussionmentioning
confidence: 84%